Immunohistochemical Study of Glucose Transporter GLUT-5 in Duodenal Epithelium in Norm and in T-2 Mycotoxicosis - Piret Hussar; Florina Popovska-Percinic; Katerina Blagoevska; Tõnu Järveots; Ilmārs Dūrītis (Foods, 2020)
Although patterns of glucose transporter expression and notes about diseases leading to adaptive changes in intestinal fructose transport have been well-characterized, the connection between infection and fructose transportation has been lightly investigated. Up to now only few studies on GLUT-5 expression and function under pathological conditions in bird intestines have been carried out. The aim of our current research was to immunolocalize GLUT-5 in chicken duodenal epithelium in norm and during T-2 mycotoxicosis. Material from chicken (Gallus gallus domesticus) duodenum was collected from twelve seven-day-old female broilers, divided into control group and broilers with T-2 mycotoxicosis. The material was fixed with 10% formalin and thereafter embedded into paraffin; slices 7 μm in thickness were cut, followed by immunohistochemical staining, according to the manufacturers guidelines (IHC kit, Abcam, UK) using polyclonal primary antibody Rabbit anti-GLUT-5. Our study revealed the strong expression of GLUT-5 in the apical parts of the duodenal epithelial cells in the control group chickens and weak staining for GLUT-5 in the intestinal epithelium in the T-2 mycotoxicosis group. Our results confirmed decreased the expression of GLUT-5 in the duodenal epithelium during T-2 mycotoxicosis.